A mama for Owen - Bauer, Marion Dane (Simon & Schuster Books for Young Readers, 2007)
When the 2004 Indian Ocean tsunami separates a young African hippopotamus from his mother, he finds a new snuggle partner in Mzee the giant tortoise. Based on a true story.